2016
DOI: 10.1016/j.anifeedsci.2016.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rapeseed variety and oil extraction method on the content and ileal digestibility of crude protein and amino acids in rapeseed cake and softly processed rapeseed meal fed to broiler chickens

Abstract: A note on versions:The version presented here may differ from the published version or from the version of record. If you wish to cite this item you are advised to consult the publisher's version. Please see the repository url above for details on accessing the published version and note that access may require a subscription.For more information, please contact eprints@nottingham.ac.uk

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 29 publications
(42 reference statements)
2
21
1
Order By: Relevance
“…The overall digestibility of CP and AA in SRSM and RSM were in an agreement with previously published data for SRSM (Kasprzak et al 2016) The content of fibre in diets is an important factor in animal nutrition. The processing of feedstuffs might entrap or bind the fibre with a nutrient, and consequently reducing its digestibility (Mateos et al, 2002;Garcia et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…The overall digestibility of CP and AA in SRSM and RSM were in an agreement with previously published data for SRSM (Kasprzak et al 2016) The content of fibre in diets is an important factor in animal nutrition. The processing of feedstuffs might entrap or bind the fibre with a nutrient, and consequently reducing its digestibility (Mateos et al, 2002;Garcia et al, 2008).…”
Section: Discussionsupporting
confidence: 80%
“…Nia and Ingalls (1992) reported that the increase in content of NDF might be due to the ability of fibre to bind with dietary protein during the thermal treatment as some of the heat denaturated proteins are recovered in NDF fraction. In a previous investigation (Kasprzak et al, 2016), the soft processed PR46W21 resulted in the greatest ileal digestibility of CP (AID 0.84) and most AA such as AID of lysine 0.85, AID of arginine 0.91, AID of histidine 0.89 across SRSM of eleven different rapeseed varieties. This is consistent with the data from the current study where, across processing, the meal of PR46W21 variety had a significantly greater AID and SID of CP, arginine, isoleucine, leucine, methionine, cysteine, phenylalanine, threonine, valine, lysine and histidine (Table 2, 3) compared to DK Cabernet.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations